The ophthalmology examinations review - Wong, Tien Yin; Lim, Laurence; Sng, Chelvin (World Scientific, 2011)
Many treatments and diagnostic procedures in ophthalmology have been refined over the years. This book provides a review of the specialist ophthalmology examinations for final year ophthalmology residents and trainees. It deals primarily with key facts and topics that are important from the examination perspective